Intensification: A Resource for Amplifying Population-Genetic Signals with Protein Repeats. Issue 3 (3rd February 2017) - Chen, Jieming; Wang, Bo; Regan, Lynne; Gerstein, Mark
Abstract: Large-scale genome sequencing holds great promise for the interpretation of protein structures through the discovery of many, rare functional variants in the human population. However, because protein-coding regions are under high selective constraints, these variants occur at low frequencies, such that there is often insufficient statistics for downstream calculations. To address this problem, we develop the Intensification approach, which uses the modular structure of repeat protein domains to amplify signals of selection from population genetics and traditional interspecies conservation. In particular, we are able to aggregate variants at the codon level to identify important positions in repeat domains that show strong conservation signals. This allows us to compare conservation over different evolutionary timescales. It also enables us to visualize population-genetic measures on protein structures. We make available the Intensification results as an online resource (http://intensification.gersteinlab.org ) and illustrate the approach through a case study on the tetratricopeptide repeat. Graphical Abstract: Highlights: Large-scale genome sequencing discovered many, rare variants, which occur at such low frequencies in the human population that there is often insufficient statistics for downstream population-genetic computation. The Intensification approach uses the genomic coordinates and the modular structure of repeat protein domains to help amplify signals of selection derived from population genome sequencing and conventional interspecies conservation. Intensification can identify important positions in repeat domains and protein structures that show strong conservation using a combination of conserved positions in motif-MSA and amplified signals in population-genetic measures. We provide an online resource (http://intensification.gersteinlab.org) and illustrate the approach through a case study using the tetratricopeptide repeat.